A novel design of printable tunable stiffness metamaterial for bone healing. (April 2021) - Hashemi, Mohammad Saber; McCrary, Aaron; Kraus, Karl H.; Sheidaei, Azadeh
Abstract: A tunable stiffness bone rod was designed, optimized, and 3D printed to address the shortcomings of existing bone fixation devices, such as stress shielding and bone nonunion in the healing of fractured bones. Current bone plates/rods have constant and high stiffness. High initial stiffness prevents the micromotion of newly formed bone and results in poor bone healing. Our novel design framework provides surgeons with a ready-for-3D-printing, patient-specific design, optimized to have the desired force-displacement response with a stopping mechanism for preventing further deformation under higher-than-normal loads, such as falling. The computational framework is a design optimization based on the multi-objective genetic algorithm (GA) optimization with the FE simulation to quantify the objectives: tuning the varied stiffness while minimizing the maximum von Mises stress of the model to avoid plastic and permanent deformation of the bone rod. The computational framework for optimum design of tunable stiffness metamaterial presented in this paper is not specific for a tibia bone rod, and it can be used for any application where bilinear stiffness is desirable.